2020
DOI: 10.1002/ijgo.13304
|View full text |Cite
|
Sign up to set email alerts
|

The association between race/ethnicity and peripartum hysterectomy and the risk of perioperative complications

Abstract: Objective To compare perioperative outcomes by patient race/ethnicity. Methods A retrospective cohort study identified 7 331 638 childbirth hospitalizations for women aged 12–55 years in the USA between 2004–2014. Peripartum hysterectomy, in‐hospital mortality, perioperative complications, length of stay, and cost of hysterectomy data were analyzed using SAS. Results Among childbirth hospitalizations (52.9% white, 13.5% black, 23.0% Hispanic, 5.2% Asian, and 5.4% other), peripartum hysterectomy occurred in 661… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 54 publications
0
3
1
Order By: Relevance
“…This may be in association with the indication for peripartum hysterectomy, which, in Black women, was more likely to be nonelective/emergent and less likely to have risk-appropriate perioperative evaluation resulting in uncontrolled hemorrhage. Although we found the proportion of Black women being readmitted within 30 days was higher than their White counterparts, there were no other statistically significant differences in adverse outcomes from peripartum hysterectomy, which have been observed in other population-level studies such as increased risk of blood transfusion 4 or surgical site infection. 16 Fewer disparities in outcome measures at our institution may be due to either a smaller sample size or the greater availability of resources to treat the most emergent cases.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…This may be in association with the indication for peripartum hysterectomy, which, in Black women, was more likely to be nonelective/emergent and less likely to have risk-appropriate perioperative evaluation resulting in uncontrolled hemorrhage. Although we found the proportion of Black women being readmitted within 30 days was higher than their White counterparts, there were no other statistically significant differences in adverse outcomes from peripartum hysterectomy, which have been observed in other population-level studies such as increased risk of blood transfusion 4 or surgical site infection. 16 Fewer disparities in outcome measures at our institution may be due to either a smaller sample size or the greater availability of resources to treat the most emergent cases.…”
Section: Discussioncontrasting
confidence: 65%
“…[8][9][10] We sought to characterize a cohort who underwent peripartum hysterectomy between 2008 and 2018. We evaluated whether risk factors identified in prior literature, such as previous cesarean delivery and placental abnormality, [1][2][3][4][5][6] were also significant within our cohort, or if other factors, such as preeclampsia, contributed an increased risk for peripartum hysterectomy. We also examined whether differences in morbidity-and mortality-related outcomes were present for patients undergoing peripartum hysterectomy with respect to certain demographic factors such as race/ethnicity, ZIP code, or insurance type.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of SMM incidence timing-differences amongst racial and ethnic groups between 2010 and 2014 found that during delivery hospitalization there was a gap in SMM between non-Hispanic-White women and all others, but during the six weeks after delivery hospitalization discharge, only the Black-White gap remained [9 ▪ ]. Studies examining individual SMM indicators show that peripartum hysterectomy, perioperative blood transfusions, and intensive care unit (ICU) admissions have increased rates for Black and Hispanic women (and other non-White women) [10–12]. NIS analysis of data between 2007 and 2017 showed that Black women, compared to White women, had the highest adjusted odds of major cardiovascular events (mortality, myocardial infarction, stroke, pulmonary embolism, peripartum cardiomyopathy) among pregnant and postpartum women [13 ▪ ].…”
Section: Epidemiology Of Obstetrical Disparitiesmentioning
confidence: 99%
“…Previous literature has demonstrated an association between race/ethnicity and peripartum hysterectomy [22][23][24][25], and evaluated trends over time [2,11,22,26]. However, these studies do not assess potential temporal variation in hysterectomy rates or investigate factors that may contribute to race/ethnicity-specific trends.…”
Section: Introductionmentioning
confidence: 99%